Transcriptome sequencing revealed that knocking down FOXL2 affected cell proliferation, the cell cycle, and DNA replication in chicken pre-ovulatory follicle cells. - Wei Luo; Lantao Gu; Jinqiu Li; Yanzhang Gong (PLoS ONE)
Forkhead box L2 (FOXL2) is a single-exon gene encoding a forkhead transcription factor, which is mainly expressed in the ovary, eyelids and the pituitary gland. FOXL2 plays an essential role in ovarian development. To reveal the effects of FOXL2 on the biological process and gene expression of ovarian granulosa cells (GCs), we established stable FOXL2-knockdown GCs and then analysed them using transcriptome sequencing. It was observed that knocking down FOXL2 affected the biological processes of cell proliferation, DNA replication, and apoptosis and affected cell cycle progression. FOXL2 knockdown promoted cell proliferation and DNA replication, decreased cell apoptosis, and promoted mitosis. In addition, by comparing the transcriptome after FOXL2 knockdown, we found a series of DEGs (differentially expressed genes) and related pathways. These results indicated that, through mediating these genes and pathways, the FOXL2 might induce the cell proliferation, cycle, and DNA replication, and play a key role during ovarian development and maintenance.